Precarity and Enterprising Selves: The Resemiotization of Neon Language Objects. (March 2021) - Joseph Theng, Andre
Abstract: Following my observation of an increased prevalence of neon or neon-esque signs within high-end spaces of consumption, this paper seeks to theorise how such signs can function as vehicles for the circulation of neoliberal ideas, a key concept structuring the capitalist economies, whilst having effects for individuals who are sold a brand of cool capitalist consumption. I demonstrates how neoliberalism is semiotically realised both online and offline through examples of "language objects" consisting of neon signs found in cafes located in Hong Kong and Singapore, and their Instagram resemiotizations, focusingon dimensions of precarity and the entrepreneurial self. In doing so, I suggest that these signs are not merely aphorismic decor but a means to reproduce neoliberal ideology in both their medium and message when they stylise concepts of individual agency, success and the turning of everyday activities into "projects". Instead of the transformation and success promised by these stances, these signs further obscure the social embeddedness of neoliberalism and resulting inequality.